The Nature Of The Connection Between A Counselor's Effectiveness, Level Of Education, And Social Environment - Onyekeshini, Blessing Ishioma; Onoshakpokaiye, Odiri E. (UIN Siber Syekh Nurjati Cirebon, 2025)
This study investigates how the social environment and educational qualification influences the effectiveness of counsellors. The study adopted a correlational design. The population of the study comprised all 270 school practicing counsellors from 472 public schools in Delta State, Nigeria. All the 270 school practicing counsellors in Delta State were used as sample, because the size was manageable. A questionnaire was the tool utilized in this investigation. Two research questions and two hypotheses were used for the study. Drawing from empirical studies, it explores factors such as institutional support, community attitudes, resource availability, and socio-cultural dynamics. While previous literature often emphasizes the influence of environmental factors on counselling outcomes, this research critically evaluates whether such influence is statistically significant. Using empirical data, the study finds that counsellors’ effectiveness may be more strongly linked to personal competencies and institutional frameworks than to broader social environmental factors. The findings reveal a significant relationship between social environment and counsellors’ effectiveness. It also revealed that the effectiveness of counselors and their level of education are not significantly correlated. The findings suggest that the social environment plays a pivotal role in shaping counsellors’ performance, motivation, and impact. Some recommendations were made.Keywords: Counselor's Effectiveness, Level Of Education, Social Environment